The impact of prolonged landscape fire smoke exposure on women with asthma in Australia - Tesfalidet Beyene; Vanessa E. Murphy; Peter G. Gibson; Vanessa M. McDonald; Joe Van Buskirk; Elizabeth G. Holliday; Anne E. Vertigan; Jay C. Horvat; Graeme R. Zosky; Geoffrey G. Morgan; Edward Jegasothy; Ivan Hanigan; et al. (BMC Pregnancy and Childbirth, 2022)
Abstract Background Little is known about the physical and mental health impact of exposure to landscape fire smoke in women with asthma. This study examined the health impacts and information-seeking behaviours of women with asthma exposed to the 2019/2020 Australian fires, including women who were pregnant. Methods Women with asthma were recruited from the Breathing for Life Trial in Australia. Following the landscape fire exposure period, self-reported data were collected regarding symptoms (respiratory and non-respiratory), asthma exacerbations, wellbeing, quality of life, information seeking, and landscape fire smoke exposure mitigation strategies. Participants’ primary residential location and fixed site monitoring was used to geolocate and estimate exposure to landscape fire-related fine Particulate Matter (PM2.5). Results The survey was completed by 81 pregnant, 70 breastfeeding and 232 non-pregnant and non-breastfeeding women with asthma. Participants had a median daily average of 17 μg/m3 PM2.5 and 105 μg/m3 peak PM2.5 exposure over the fire period (October 2019 to February 2020). Over 80% of participants reported non-respiratory and respiratory symptoms during the fire period and 41% reported persistent symptoms. Over 82% reported asthma symptoms and exacerbations of asthma during the fire period. Half the participants sought advice from a health professional for their symptoms. Most (97%) kept windows/doors shut when inside and 94% stayed indoors to minimise exposure to landscape fire smoke. Over two in five (43%) participants reported that their capacity to participate in usual activities was reduced due to prolonged smoke exposure during the fire period. Participants reported greater anxiety during the fire period than after the fire period (mean (SD) = 53(13) versus 39 (13); p < 0.001). Two in five (38%) pregnant participants reported having concerns about the effect of fire events on their pregnancy. Conclusion Prolonged landscape fire smoke exposure during the 2019/2020 Australian fire period had a significant impact on the health and wellbeing of women with asthma, including pregnant women with asthma. This was despite most women taking actions to minimise exposure to landscape fire smoke. Effective and consistent public health messaging is needed during landscape fire events to guard the health of women with asthma.